Perinatal guanacos (Lama guanicoe) exploited by hunter‐gatherers from the Holocene of Argentine Pampas - Frontini, Romina (2018)
The guanaco (Lama guanicoe) was the most relevant species in hunter-gatherer subsistence of the Argentine Pampas during the Quaternary. An early Late Holocene (3,184 ± 50 14C years bp) guanaco assemblage with evidence of exploitation, coming from Cerro del Águila site, Buenos Aires Province, is analysed herein. The assemblage is composed by three perinatal individuals; the estimated age at the moment of death ranges from a few weeks before birth to a few weeks old. Cerro del Águila is interpreted as a site where activities of procurement and processing of perinatal individuals were performed. The available information allows raising a discussion on the hunting and exploitation strategies of guanaco in a regional context.